(3GdJYqSa aj GSJYeGd Mb GdJbGVj aj GdTQjYI GdESdGejI h GdbGfhf GdhVYj (B: s (3OQGSI ebGQfI (B/ s - (3CfS eMehO GdbWGfs; (3eMeO jhSa Mafj (B: s; (3eMehO YHOGdQMef (B: s ((3GdbGgQI (B: s (3CfS eMehO GdbWGf (B: s, 2015)
(3Ef GdbGQF ddJQGK GdESdGej jLO Cf fXQjI GdJYSa aj GSJYeGd GdMb de JZH Yf CPgGf abgGA GdeSdejf(B. (3abO GcJedJ eYGde gPg GdfXQjI dOjge efP GdbQf GdSGOS GdgLQj(B: (3hef Ke abO JfGhdgG HGdPcQ hGdTQM GdabgGA hYdeGA GdCUhd hZjQge aj eDdaGJge heUfaGJge(B. (3hdgPG(B: (3SYJ gPg GdOQGSI Edi GdJCUjd dehVhY GdJYSa aj GSJYeGd GdMbhb(B: (3dGSjeG Mb GdJbGVj aj cd ef Gdabg GdESdGej hGdbGfhf GdhVYj ef NdGd GSJbQGA GdfUhU GdeJYdbI HPdc aj GdeUGOQ PGJ GdUdI(B. (3hbO cTaJ GdOQGSI Yf hLhO acQI GdJYSa aj GSJYeGd GdMb aj GdeLGd GdELQGFj aj Gdabg GdESdGej(B: (3hChVMJ Cf gPG Gdabg bO GVWdY HegeI JMOjO fWGbgG(B. (3ceG YbOJ GdOQGSI ebGQfI Hjf LhGfH GdJYSa aj GSJNOGe gPG GdMb aj Gdabg hGdbGfhf(B: (3dJHQR Cge fbGW GdGdJbGA hGdGNJdGa(B: (3eY GdJQcjR Ydi eYGdLI GdbGfhf GdchjJj dgPg GdfXQjI(B. (3hYedJ GdOQGSI Ydi HjGf UhQ GdJYSa aj GdJbGVj ef LGfH GdeOYj hGdeOYi Ydjg hGdbGVj(B: (3hGdBKGQ GdeJQJHI Ydi Pdc hYdi GdNUheGJ GdeQahYI CeGe GdbVGAs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdESdGejI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJYqSa s; (3Gdabg GdESdGejs; (3Mb GdJbGVj s